An analysis of the cases of teenagers dying in taverns in South Africa: Some Biblical and African considerations - Rev. Jacob Mokhutso (Pharos Journal of Theology, 2022)
According to the Holy Scriptures, parents must care, teach, and guide their children to lead a Godly life. Comparably, the African traditional religion expects parents to do so too. On the morning of 26 June 2022, South Africa woke up to the harrowing news of the death of twenty-one young people in a tavern in East London, in the Eastern Cape province of South Africa. Later, the number of deaths rose to twenty-two. Young people, the youngest being thirteen years old, lost their lives on this fateful day. First, this research seeks to reflect on the lessons the country should learn from this unfortunate ordeal so that such incidents do not occur again. Secondly, this research draws wisdom from the Christian teachings on parenting and African indigenous knowledge system that has anchored African communities for millennia. The research seeks to draw lessons from the teaching of the Bible and African indigenous knowledge system, exploring a Setswana proverb, Ngwana sejo o a tlhakanelwa, meaning a child is a food around which we all gather, implying that a child's upbringing is a communal responsibility. This research also argues that the Enyobeni Tavern incident reflects that Black African families, communities, and the Church’s societal role have changed over the years and how these changes harm their social fabric. The research uses a literature review as a research method to formulate the data and conclusion of the study. The research concludes that, with the change in Black African family structure and communities, some biblical and African considerations drawn from the proverb Ngwana sejo o a tlhakanelwa are relevant to mitigate various social challenges Black African communities face in South Africa.